PERAN ORANG TUA DALAM MEMBANGUN KEBIASAAN MEMBACA ALKITAB UNTUK MENINGKATKAN KECERDASAN SPIRITUALITAS ANAK KRISTEN - Joel Betakore; Graciela Sharel Tanonggi; Gabrina (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Reading the Bible is an engaging activity that significantly benefits a child's life. However, the advancement of digitalization has become an obstacle, with children preferring gadgets over the Bible. This is where the role of parents becomes crucial in rebuilding the habit of reading the Bible. This study examines the role of parents in establishing the habit of reading the Bible to enhance the spiritual intelligence of Christian children. Using a descriptive qualitative approach, data was collected from relevant journals and compiled to strengthen the analysis. Findings indicate that the habit of reading the Bible not only reinforces the child's faith foundation but also teaches essential moral and ethical values. Effective parental communication and support have been shown to strengthen emotional bonds and boost children's confidence. Good spiritual education helps children develop critical thinking skills, empathy, and mental resilience and provides guidance in life decision-making. This study emphasizes the crucial role of parents in spiritual education for the better future of their children.